Queering the Dialogue: How Young Adults Are Redefining Sex and Safe Sex - Thea Roland (The Journal for Undergraduate Ethnography)
On liberal arts campuses across the United States, about 40% of students are identifying as LGBTQ+ according to a study cited by The College Fix (Peppiatt 2022). While many surveys have collected data on the sexual orientations of students, few have assessed how students are having sex and what safe sex measures they may be using. In a cultural climate that discourages sexual knowledge and offers limited sex education, young adults are defining sex and sexual safety for themselves. This research is framed in the context of symbolic interactionism, discourse theory, and sexual scripts. This research uses eight interviews with liberal arts college students, predominantly queer, to glean personal experiences of sexual learning, sexual safety, and their perceptions and definitions of ‘sex.’ This study suggests that young adults have reacted to heteronormative norms and limited sexual education with their own dialogical understandings of sex and sexual safety which I consider a ‘queering of the dialogue.’ The results demonstrate that current approaches to sexual education set young adults up for unsafe sex and that dialogue is an integral tool for sexual safety and the vastness of queer sex.